Propagación de frutales por injerto y su adopción en los huertos de Huayo, Pataz, La Libertad - Colchado López, Olger Pascual (2017)
The study describes the procedure of grafting mango, avocado and apple, for its diffusion into 44 and 43 homegardens from Pan de Azúcar annexed, and Pucabamba annexed respectively, both located at Huayo district of Pataz, La Libertad. Besides, it was measured the adoption of grafts by farmers, and surveys were carried out to explain the level of adoption because of socioeconomic characteristics of farmer, characteristics of the orchard, and technical assistance._x000D_ Mango and avocado rootstocks raised from collected seeds in Chagual homegardens, located at the south of Pataz district. The scions were mango ‘Kent’ and avocado ‘Fuerte’, both bought at a plant nursery located in Virú. They were grafted apple Israel scions onto yellow creole quince, selected from homegardens in Huayo. Rootstocks propagation was by cutting from selected mother plant grown on homegardens in Huayo. The method used was the cleft graft in the three fruit species. Fungicide against soil fungal populations disinfected seeds and cuttings. A 65 % shade raschel net protected seedlings and grafted plants all propagation phase long, other cares were foliar feeding application and pesticide application against aphids and Trichoplusia ni, as well as, light and frequent irrigation._x000D_ It was found out that (1) Mango, avocado and apple tree propagated by grafting had a 93, 93 y 92% graft success respectively; (2) Adoption of grafted plants in homegardens from Pan de Azúcar was 82% while, in Pucabamba, it was 81%. (3) Fruit cropping are low consumption of agricultural inputs and technical criterion is absent